The minimum wage versus the earned income tax credit for reducing poverty - Richard V. Burkhauser; Kevin Corinth (IZA World of Labor, 2021)
Minimum wage increases are not an effective mechanism for reducing poverty. And there is little causal evidence that they do so. Most workers who gain from minimum wage increases do not live in poor (or near-poor) families, while some who do live in poor families lose their job as a result of such increases. The earned income tax credit is an effective way to reduce poverty. It raises only the after-tax wage rates of workers in low- and moderate-income families, the tax credit increases with the number of dependent children, and evidence shows that it increases labor force participation and employment in these families.
Keywords: J23; J39; J88; I38; I32; 330; minimum wage; earned income tax credit; working poor